İKİ DOĞRU AKIM MOTORUNUN AYNI YÜKÜ BESLEMESİ DURUMUNUN BOND GRAF YÖNTEMİ'YLE İNCELENMESİ - YILDIZ, ABDULNASIR (Fırat Üniveristesi, 2002)
Yüksek Lisans Tezi İKİ DOĞRU AKIM MOTORUNUN AYNI YÜKÜ BESLEMESİ DURUMUNUN BOND GRAF YÖNTEMİYLE İNCELENMESİ Abdulnasır YILDIZ Fırat Üniversitesi Fen Bilimler Enstitüsü Elektrik-Elektronik Mühendisliği Anabilin Dalı 2002, Sayfa: 55 Bu çalışmada, iki doğru akım motorunun aynı yükü beslemesi durumu bond graf yöntemiyle incelendi Bu inceleme yapılırken iki doğru akım motorunun paralel ve seri bağlı durumları ayrı ayrı ele alındı. Bu amaçla önce bond graf modeli tanıtıldı. Daha sonra her iki sistemin bond graf modelleri elde edüdi Ardından bu modelleri kullanarak simülasyon yapan Enport programı ile sistemlerin endüvi akımları ve açısal hızlarının zamana göre değişimlerinin grafiksel sonuçlan elde edildi Son olarak da sistemlerin bond graf modelleri kullanılarak elde edilen Enport simülasyon sonuçlarının doğruluğunu göstermek için aynı sistemlerin Matlab simülasyon sonuçları elde edildi. ANAHTAR KELİMELER: Bond Graf, Enport, Matlab

m ABSTRACT Masters Thesis INVESTIGATION OF THE SITUATION OF THE FEEDING THE SAME LOAD WITH TWO DIRECT-CURRENT MOTORS, BY BOND GRAPH METHOD Abdulnasir YILDIZ Fırat University Graduate School of Natural and Applied Sciences Depertment of Electriciai and Electronics Engineering 2002, Page: 55 In this thesis, the case of the two direct-current motors feeding the same load was investigated by using the bond graph method. The series and parallel case of the two motors were investigated separately. For this aim, firstly, the bond graph method was introduced. Then, the bond graph models of the both systems were obtained. After then, the change of armature currents and angular velocities of the systems with respect to time was obtained graphically from the program of Enport simulation. Finally, to illustrate the accuracy of the results obtained from the Enport simulation of the systems by using the bond graph method, the Matlab simulations of the same systems were implemented, and results were compared. KEY WORDS: Bond Graph, Enport, Matlab.
Investigation of the situation of the feeding the same load with two direct-current motors, by Bond Graph Method
Keywords: Elektrik ve Elektronik Mühendisliği; Electrical and Electronics Engineering